2018
DOI: 10.1634/theoncologist.2018-0573
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Taxane-Based Therapy in Small Bowel Adenocarcinoma

Abstract: Currently, treatment of small bowel adenocarcinoma (SBA) mirrors that of colorectal cancer (CRC). Recent genomic data have demonstrated SBA to be a genetically unique entity, suggesting that therapies not traditionally utilized in CRC should be explored. In order to further characterize the activity of taxanes in this rare cancer, we completed a single‐center retrospective study. Twenty patients were found to have been treated with taxane‐based regimens (monotherapy in 3, combination therapy in 17). Median tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…In most studies: first-line chemotherapy was mainly 5-FU based regimens, with or without a platinum salt or irinotecan. These different regimens are shown in Table 1 and Table 2 [ 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 ].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies: first-line chemotherapy was mainly 5-FU based regimens, with or without a platinum salt or irinotecan. These different regimens are shown in Table 1 and Table 2 [ 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 ].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…Two other small studies suggested clinical activity for taxane-based therapy in advanced SBA after first-line chemotherapy [ 19 , 28 ]. In a retrospective study, Aldrich et al reported the results from taxane-based therapy in 20 patients demonstrating an ORR of 65% and a median PFS and OS of 3.8 and 10.7 months, respectively [ 28 ].…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…This finding, which has been identified in a few small reports, supports the inclusion of taxane-based chemotherapy as an option beyond the first line in the NCCN guidelines. 8 , 25 , 26 , 27 Though used in a limited number of patients, neither TAS-102 nor regorafenib appeared to demonstrate meaningful activity with best response of PD seen in four of the five patients.…”
Section: Discussionmentioning
confidence: 88%
“…132 A single-center, retrospective review reported on 20 patients with advanced SBA who were treated with taxane-based therapy (either as single therapy or in combination). 133 Of these cases, 30% showed disease response, 35% showed stable disease, and 35% showed progression. Median time to progression was 3.8 months (95% CI, 2.9-4.6) and median OS was 10.7 months (95% CI, 3.1-18.3).…”
Section: Taxane-based Chemotherapy As Subsequent-line Therapymentioning
confidence: 96%